1959
DOI: 10.1139/v59-243
|View full text |Cite
|
Sign up to set email alerts
|

THE STUDY OF ELECTRICALLY DISCHARGED O2 BY MEANS OF AN ISOTHERMAL CALORIMETRIC DETECTOR

Abstract: AIolecular osygen \\-as subjected to an electrodeless discharge in the pressure range 0.1-3 111111 Mg. The osygen atoll1 concentration was measured as a function of time in a flo\\. system by means of a mo\~able atom cletector which consisted of a platinum wire coatecl with a suitable catnI!.st for atoll1 reco~nbination. The atom concentration was calculated fro111 the heat liberated \\-hen the detector was operated under isother~nal conditions. The surface recombi~la-tion \vas found to be first order in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1959
1959
1988
1988

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 133 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…Indeed, this effect has been observed with Ar and He additions to O 2 plasmas. 33 In experiments involving Ar addition to NH3 plasmas however, no enhancement of NH + NH z concentrations is observed, implying that the role of added H2 is to react with NH3 to enhance dissociation. Gas phase dissociation may also be affected by changes in the electron energy distribution function, resulting from varying the gas phase composition (Le., Hz addition), Mixtures ofN z and Hz also yield significant concentrations ofNH and NH z radicals, although the levels are lower than in pure NH3 plasmas.…”
Section: B Gas Phase Neutral Mass Spectroscopymentioning
confidence: 99%
“…Indeed, this effect has been observed with Ar and He additions to O 2 plasmas. 33 In experiments involving Ar addition to NH3 plasmas however, no enhancement of NH + NH z concentrations is observed, implying that the role of added H2 is to react with NH3 to enhance dissociation. Gas phase dissociation may also be affected by changes in the electron energy distribution function, resulting from varying the gas phase composition (Le., Hz addition), Mixtures ofN z and Hz also yield significant concentrations ofNH and NH z radicals, although the levels are lower than in pure NH3 plasmas.…”
Section: B Gas Phase Neutral Mass Spectroscopymentioning
confidence: 99%
“…The origin of the lines at 6350 A and 7030 A is more mysterious. It should be noted that a q u a n t u m at 6350 A has precisely twice the energy of one at 12,700 A and it has been suggested that the line at 6350 A is emitted by the transitions of dimers of IA oxygen (o2(1~))2 --, (o2(,z))~ + h~ (6) and that at 7030 A has the same origin but involves also a change in vibrational state. In any event, the spectroscopic work makes it certain that electronically excited molecules are produced in the reaction although the yield has not yet been specified.…”
Section: Reactions Of Electronically Excited Oxygenmentioning
confidence: 99%
“…The rate of production of O,(lAg) was varied by changing the 0, flow and the discharge power. The discharge products were passed over a glass wool plug containing mercuric oxide in ordkr to remove atomic oxygen (6). This removal was essential since the 0 atoms associatively detach electrons from both 0,-and 0-(2).…”
mentioning
confidence: 99%